(untitled) (Strathmore Law Review, 2020)
Constitutions do not make revolutions. Revolutions make constitutions. No constitution envisages its own death for that is what a revolution entail. But constitutions matter. Some of the finest constitutions have been erected on ugly socio-economic formations wrought with extreme inequalities and inequities. South Africa and Kenya are examples. But constitutions do matter. Constitutions rarely herald fundamental transformations. They are the product of major transformations to consolidate the new status quo. Yet constitutions do matter. Why do constitutions matter? Why do we need constitutions? Why does every revolution and major change in modern societies birth new constitutions?